The European Union as a global actor - Bretherton, Charlotte; Vogler, John. (New York : Routledge, 1999)
"This book is the first sustained analysis of the EU in global politics. It reveals that the EU is a multifaceted and variable actor, which cannot be fitted into any orthodox template of a nation state. Issues covered include how the field of trade relations forms the basis of the EU's activities, and the EU's controversial relationship to CFSP and defense."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: European Union countries -- Foreign relations